Writing Yourself Home: US Veterans, Creative Writing, and Social Activism - Frank Usbeck (European Journal of American Studies)
The post-9/11 wars have brought forth a new generation of military veterans in the US and rekindled debates about social and psychological problems related to war experience. These veterans produced a plethora of firsthand war narratives in diverse genres and media. This article explores how public discourse about civil-military relationships, war experience, and trauma, simmering since the domestic divisions over Vietnam, turned to such first-person narratives in recent years to discuss the psychological costs of war and homecoming. It interprets the proliferation of veterans’ writing projects as part of a civic activist movement that, postulating a social crisis in civil-military relationships, seeks to address veterans’ social and emotional struggles through community (re)building and social therapy. The writing projects promote themselves as a means to bridge the experiential gap between civilians and veterans and, in doing so, they enact social reintegration.